'Kimberley Stout figures': a new rock art style for Kimberley rock art, North-Western Australia. Issue 2 (4th May 2019) - Gunn, Robert; David, Bruno; Douglas, Leigh; Delannoy, Jean-Jacques; Harper, Sam; Heaney, Pauline; Ouzman, Sven; Veth, Peter
Abstract: The rock art of Western Australia's Kimberley region has been the subject of special attention by archaeologists and rock art enthusiasts since George Grey's publication of the first illustration of it. Since then, researchers have tried to date and classify the Kimberley's many rock art styles. To date, eight widespread and highly recognisable styles have been identified, but many motif types in a range of styles remain undescribed and lie outside the formally recognised art styles. While undertaking archaeological work at Borologa, a highly decorated rock shelter in the Balanggarra lands of the north-east Kimberley, we documented a distinctive set of anthropomorphic figures that stood out for their characteristic formal and decorative attributes. Here termed 'Kimberley Stout figures', we propose this as a distinct motif type undertaken in a hitherto undescribed style within the Kimberley rock art corpus, describing its attributes in depth and discussing its positioning within the Kimberley rock art sequence.